Batik pesisir pusaka Indonesia koleksi Hartono Sumarsono - Ishwara, Helen 1944- (Kepustakaan Populer Gramedia, 2011)
Catalog and descriptions of the rare batik pesisir collections of Hartono Sumarsono, an Indonesian batik collector